Thermoelectric and optical properties of CuAlO2synthesized by direct microwave heating - Tawat Suriwong (2018)
A single phase of delafossite CuAlO2(CAO) was successfully synthesized by a 600 W microwave radiation for 20 min. The CAO sample was composed of quite distorted single-crystalline plates with 200-350 nm thick. Its atomic vibrations were detected at 760 and 550 cm-1belonging to Al-O and Cu-O stretching, respectively. The direct and indirect energy gaps were respectively determined to be 3.9 and 2.9 eV. The photoluminescence (PL) at room temperature was at 585 nm (2.12 eV) corresponding to the indirect energy gap and at 760 nm (1.63 eV) corresponding to the p-type native defect. For its thermoelectric (TE) properties, the Seebeck coefficient (S) was positive value, with holes as the majority of charge carriers. By increasing of the test temperature, both the electrical resistivity and absolute value of Seebeck coefficient were decreased, but the power factor was in the opposite manner. The dimensionless figure of merit (ZT) of the crystalline CAO was evaluated to be the maximum of 9 × 10-3at 1073 K. © 2014 Elsevier B.V. All rights reserved.